Reflections on the Development of Modular Data Center - Yan Hu (Dianxin kexue)
The development background of modular data center, and the main problems of the traditional data center were firstly analyzed. Then the key technology of modular data center was described. Finally, the promotion suggestions of modular data center were put forward.